2017
DOI: 10.1108/el-09-2015-0170
|View full text |Cite
|
Sign up to set email alerts
|

Digital preservation policies of the institutional repositories at Brazilian Federal Universities

Abstract: Purpose-This article aims to verify the implementation of digital preservation policies at the institutional repositories of Brazilian Federal Universities. Design/methodology/approach-The methodology used involved the verification of the information available in the Directory of Open Access Repositories (OpenDOAR) and on the websites of the institutional repositories, in order to confirm the existence of published digital preservation policies. We used a sample of the 26 institutional repositories of Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…The study revealed that 32 (26 per cent) ARL institutions currently have a digital preservation policy in place, from the institutions that responded (58 per cent response rate). On the other hand, the study by da Silva Júnior and Borges (2017) revealed that the IRs at Brazilian Federal Universities registered at the OpenDOAR do not have any preservation policies, even though all the repositories that have implemented the IBICT-IIP (Brazilian Institute for Information in Science and Technology- institutional information policy) framework state their intention of preserving digital materials. Da Silva Júnior and Borges (2017) therefore concluded that a digital preservation policy would need to be drawn up in coordination with the staff in charge of the repository and the managers of the collections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that 32 (26 per cent) ARL institutions currently have a digital preservation policy in place, from the institutions that responded (58 per cent response rate). On the other hand, the study by da Silva Júnior and Borges (2017) revealed that the IRs at Brazilian Federal Universities registered at the OpenDOAR do not have any preservation policies, even though all the repositories that have implemented the IBICT-IIP (Brazilian Institute for Information in Science and Technology- institutional information policy) framework state their intention of preserving digital materials. Da Silva Júnior and Borges (2017) therefore concluded that a digital preservation policy would need to be drawn up in coordination with the staff in charge of the repository and the managers of the collections.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the study by da Silva Júnior and Borges (2017) revealed that the IRs at Brazilian Federal Universities registered at the OpenDOAR do not have any preservation policies, even though all the repositories that have implemented the IBICT-IIP (Brazilian Institute for Information in Science and Technology- institutional information policy) framework state their intention of preserving digital materials. Da Silva Júnior and Borges (2017) therefore concluded that a digital preservation policy would need to be drawn up in coordination with the staff in charge of the repository and the managers of the collections. Such a policy would need to be approved by the highest university authorities and that would also imply the assumption of a real commitment from the institution towards digital preservation issues.…”
Section: Resultsmentioning
confidence: 99%
“…In Korea, a consortium called the Korean Education and Research Information Service (KERIS) has been established to organize the IR of a number of universities into a single platform called “dCollection” (Digital Collection) to give users more access to information resources (Hee Kim and Ho Kim, 2008). Brazilian Federal Universities have also joined the global move of establishing IR to give visibility to their intellectual output (Da Silva and Borges, 2017). USA, Spain and Africa have all recorded a massive adoption of IR in their universities (Fralinger and Bull, 2013; Serrano-Vicente et al , 2018; Dlamini and Snyman, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main challenge IR manager's face right now is to keep an IR dynamic without losing these features, and it is directly linked to the policies and procedures that it adopts. In Brazil, even if some of the repositories of universities have started their preservation purpose, most of them have not published digital preservation policies in their repositories (da Silva Júnior and Manuel Borges, 2017). Globally, most repositories, which are archiving ETDs have not defined metadata, content submission and preservation policies (Loan and Yaseen, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%